Electric Forklift Drivetrain Optimization Design - Zhang Haibo; Gao Liang (Jixie chuandong)
In order to improve the range of the electric forklift and climbing performance, a transmission scheme with a two speed gearbox was proposed in this study. First of all, based on the external characteristics and efficiency characteristics of the drive motor, a two-speed transmission system parameter matching method was proposed. Secondly, taking an electric forklift as the research object, its drive system was changed: on the basis of not changing the various parameters of the driving motor, change the transmission system from one gear to two gears, and match the main reduction ratio and the two gear reduction ratios of the transmission. Finally, using ADVISOR software to counterbalance electric forklift driving cycles simulation analysis. Results show that installing a two speed gearbox without changing the parameters of the driving motor can improve the power performance and fuel economy of the whole electric forklift; the acceleration time from zero to the maximum speed increases by 0.4 seconds, the full load climbing slope increases by 2.5%, and the battery energy consumption of the 2-hour equivalent working cycle of the forklift decreases by 3.5%.